Quality of life of patients with primary open-angle glaucoma, primary angle closure glaucoma, and pseudoexfoliation glaucoma in Central Serbia - Marčeta, Elizabeta; Šarenac Vulović, Tatjana; Petrović, Nenad; Vulović, Dejan; Trenkić, Marija; Randjelović, Danijela; Todorović , Dušan (Vojnosanitetski pregled, 2023)
Background/Aim. Impaired vision resulting from glaucoma can have deleterious effects on both physical and mental health. This study aims to examine the adverse impacts of primary open-angle glaucoma (POAG), primary angle closure glaucoma (PACG), and pseudoexfoliation glaucoma (PEG) on the quality of life (QoL) in Central Serbia. Methods. This research, designed as a cross-sectional study, included 102 patients treated for POAG, PACG, or PEG. The patients were divided into three groups (POAG, PACG, and PEG) based on the type of glaucoma they suffered from and were monitored for six months. The data on the QoL were obtained with the National Eye Institute Visual Functioning Questionnaire 25 (NEI VFQ-25). Using the appropriate algorithm, the total NEI VFQ-25 scores were calculated for each group. Results. The questionnaire showed that scores for general vision were significantly lower in the PEG group than in the other two groups (PEG: 61.1 ± 12.6; POAG: 71.6 ± 17.9; PACG: 75.7 ± 11.6), p < 0.001. General health, eye pain, distance vision, social functioning, peripheral vision, reduced ability in daily activities, and dependence on others were also statistically significantly lower in the PEG group. The highest value of near vision was recorded for the POAG group (76.2 ± 21.2). The highest mean value in glaucomatous visual field defect was recorded in the PEG group (14.5 ± 3.6 dB). Conclusion. This research has demonstrated that the QoL is significantly lower in patients suffering from PEG compared to those suffering from POAG and PACG. Concerning the general health of patients, eye pain, distance vision, as well as the domain of social and everyday functioning, the lowest scores for individual areas of examination according to the NEI VFQ-25 were recorded in PEG patients. The results indicate that serious measures should be taken in order to improve the QoL of glaucoma patients.
Keywords: glaucoma, open-angle; glaucoma, angle-closure; exfoliation syndrome; quality of life; surveys and questionnaires